MATRICANÍŃ JORDAN NORMAL FORMASÍ - Kalekeeva, T.T.; Djumabekova, Z.J. (SCIENCE and SOCIETY, 2023)
In this article, the Jordan normal form of a matrix is constructed by solving matrix polynomials in several examples.